Calibration of the DOE lens array based multipoint diffraction strain sensor - Zhu, Hui (2013)
Multipoint Diffraction Strain Sensor (MDSS) is a non-contact whole field strain sensing system. DOE-based lens arrays are designed and used to replace the typical micro-lens array in our MDSS system. These DOE patterns are displayed on the liquid crystal spatial light modulator. So with different focal length, tunable strain sensitivity is achieved. Calibrations are performed to test the measurement accuracy and precision of the system.